2019
DOI: 10.1111/ejss.12786
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting responses after fires of the source components of soil respiration and ecosystem respiration

Abstract: Wildfire is an important ecological disturbance that can have cascading effects on ecosystem carbon (C) fluxes. Ecosystem respiration (ER) and soil respiration (SR) account for two of the largest terrestrial C fluxes to the atmosphere, and they play critical roles in regulating C–climate feedbacks. Here, the responses of ER, SR and their source components to experimental burning in a meadow grassland on the Tibetan Plateau were investigated. Fire treatment increased ER by 9% but decreased SR by 15%. The contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…During compound drought and fire events, there are evidence to support the occurrence of such phenomenon. The larger inhibition in Reco than in GPP could be explained by suppressed microbial soil respiration, which has also been found in previous studies in the post-drought and post-fire periods (Selsted et al 2012, Kopittke et al 2014, Chen et al 2019, Huang et al 2021. Further evidence, especially from intensive in-situ measurements, is critically needed to confirm this finding.…”
Section: Discussionsupporting
confidence: 76%
“…During compound drought and fire events, there are evidence to support the occurrence of such phenomenon. The larger inhibition in Reco than in GPP could be explained by suppressed microbial soil respiration, which has also been found in previous studies in the post-drought and post-fire periods (Selsted et al 2012, Kopittke et al 2014, Chen et al 2019, Huang et al 2021. Further evidence, especially from intensive in-situ measurements, is critically needed to confirm this finding.…”
Section: Discussionsupporting
confidence: 76%
“…Globally, approximately half the average annual flux of 2.0 Pg C yr -1 has been emitted due to fires in forest ecosystems between 1997 and 2009; 20 of these fires were from deforestation and tropical forest fires, 16 from woodland fires, and 15 from mostly extra-tropical forest fires 2001 -2009 van der Werf et al, 2010 . Although most fires in ecosystems are set by humans, a complex interaction between climate, ecosystem processes, and human activities determines fire-driven C emissions from burned areas van der Werf et al, 2010 . In tropical peatlands of Southeast Asia such as the Indonesian lowlands and Peninsular Malaysia, there are substantial fire-driven C losses in the global terrestrial C cycle Herawati and Santoso, 2011;Smith et al, 2018;Kumar et al, 2020 . For examples, the R s from burned peat surfaces increased 46 over the first nine months following a fire in the Kalimantan tropical peatland forest Astiani et al, 2018 , and a ground fire significantly stimulated R s by 17.5 for a mixed forest of sub-tropical-temperate transition zones in central China Hu et al, 2020 . Although the humid climate typical of the Asian monsoon region is relatively free from wildfire when compared to drier ecosystems in other arid or boreal ecosystems, the frequency, intensity, and size of wildfires have been increasing and is expected to increase rapidly in future given the increase in lightning strikes and seasonally extreme droughts associated with global warming Hu et al, 2017;Chen et al, 2019;Song et al, 2019. Sun et al 2014 investigated the effect of fire disturbance on R s in birch and larch forests in China, and Hu et al 2017 examined the effects of fire severity on R s in larch forests to better estimate R s in boreal ecosystems; they found that wildfires decreased R s mainly due to decreased autotrophic respiration.…”
Section: Other Natural Disturbancesmentioning
confidence: 99%
“…Sun et al 2014 investigated the effect of fire disturbance on R s in birch and larch forests in China, and Hu et al 2017 examined the effects of fire severity on R s in larch forests to better estimate R s in boreal ecosystems; they found that wildfires decreased R s mainly due to decreased autotrophic respiration. Experimental burning studies in the temperate forests of northern Japan and a Tibetan meadow grassland in China, have demonstrated that the artificial fire significantly decreases R s due to reductions in root activity, litter layer, microbial biomass and soil moisture Kim, 2013;Chen et al, 2019. Song et al 2019 found that wildfires in a montane coniferous forest decreased R s largely from the reduction in R r leading to an increase in the R h to R s ratio.…”
Section: Other Natural Disturbancesmentioning
confidence: 99%
“…However, reported observations on the effects of fire on R s rates are not consistent, with some authors reporting an increase in R s due to enhanced heterotrophic respiration rates (Hu et al, 2021;Wang, Chen, et al, 2021;Wang, Yao, et al, 2021) while others reporting a decrease due to suppressed microbial activities and reduced microbial biomass (Chen et al, 2019;Hu et al, 2023). Kong et al (2019) reported no R s changes regardless of fire intensity.…”
Section: Introductionmentioning
confidence: 97%